Knowledge, health beliefs and use of vitamin and mineral supplements among elderly clients in Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia - Ariffin, Norfaranieza Muhd (Universiti Sains Malaysia, 2009)
With the prevalence of elderly rising in the past decade, research into nutritional intake among elderly has become increasingly important. Indeed, nutrition-related health problems ranging from nutrient deficiencies to over-nutrient, makes the elderly diet is questionable. The use of nutritional supplementation is enhancing among elderly and their decision of consuming vitamin and mineral supplements might be based on personal knowledge and health beliefs. The objectives of the study is to assess the knowledge, health beliefs of the elderly and correlates them with their use of vitamin and mineral supplements among elderly clients in KRK, HUSM. This study was a cross-sectional design and descriptive study. One hundred and fifty elderly clients who were attending to KRK, HUSM were engaged in this study. From this questionnaire, the knowledge and health beliefs scores were calculated and analyzed using Statistical Package for Social Sciences version 12.0 (SPSS). Association and mean difference of the supplement usage were identified. The mean of knowledge score was 10.26 (S.D 2.21) out of possible 20. There is no association between nutritional knowledge and usage of vitamin and mineral supplements. There is no significant mean difference of knowledge score between users and non-users of vitamin and mineral supplements. The mean for health belief score was 24.4 (S.D 2.21) out 45. For the health beliefs score, the result revealed that there were no significance mean difference of health belief score between users and non-users of health belief statements. From this study, it is know that the usage of vitamin and mineral supplements still did not take place among elderly at KRK, HUSM. Besides, the findings also showed that the level of nutrition knowledge is high among the elderly. Those aspects of nutrition knowledge which are low needs improvement and those beliefs that put the elderly at risk of malnutrition in the expanding population of older adults need to be changed and further investigation of vitamin and mineral supplementation behavior in older adults should be explored.